Estudio, análisis y evaluación del acondicionamiento eléctrico, de los equipos médicos del área de imagenología del Hospital Isidro Ayora de la ciudad de Loja. - Álvarez Enríquez, Oswaldo Francisco (2012)
This present research based on the study, Analysis and Evaluation of the electric conditioning equipment of X ray and ultrasound of the Isidro Ayora Hospital, considering all referring to: electrical power, canalization, protection, control, grounding and physical space required. As these equipment’s have lots of quantities of electronics elements, they are have taken all the parameters of electric energy, such as fall of tension, super voltage, flicker, harmonics of the effects that they produce in it. The procedure was performed and development in this present research and it consist in realize a study about actual on the conditioning current that the Isidro Ayora Hospital imaging area. Where we collect all the technical data required for: transformers, plate, conductors’ types of canalization, data breakers, control elements, grounding and physical space used so like electrical data of the plate of the equipment on study. Also we realize measure of quality of electrical energy with a FLUKE 1743, giving us important data for the Analysis, the some that permit us to Know the factual of the electrical power, that using such equipment. Then we realize on Analysis of the norms of electrical installation using as reference the National Electric Code (NEC) and other international standard such as: The World Health Organization (OMS), European Norm (EN), the International Electronically Commission (IEC), and International Organization for Standardization (ISO) among others. Finally, we proceeded to carry out the Evaluation of the type of conditioning that have the medical equipment and to establish the pertinent corrections those equipment that don’t get the standards established of electrical installation.